2009
DOI: 10.1016/j.jacc.2009.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Microemboli and Microvascular Obstruction in Acute Coronary Thrombosis and Sudden Coronary Death

Abstract: Microemboli and microvascular obstruction are common in patients dying of acute coronary thrombosis. Plaque erosion is more likely to cause emboli in vessels <200 mum. These emboli and microvessel obstruction have a prominent clinical role since myonecrosis is often associated with these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(113 citation statements)
references
References 42 publications
4
109
0
Order By: Relevance
“…3,9,14, 34 Several studies have revealed the propensity of women less than 50 years old to suffer PE compared with men. 8,34- 38 Braunwald also reported a high proportion of PE in women younger than 50 years of age and premenopausal smokers. 39 Despite the different pathophysiology and demographic characteristics of PR and PE, both are similarly treated in current clinical practice with PCI and stenting.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…3,9,14, 34 Several studies have revealed the propensity of women less than 50 years old to suffer PE compared with men. 8,34- 38 Braunwald also reported a high proportion of PE in women younger than 50 years of age and premenopausal smokers. 39 Despite the different pathophysiology and demographic characteristics of PR and PE, both are similarly treated in current clinical practice with PCI and stenting.…”
Section: Discussionmentioning
confidence: 97%
“…There is greater possibility for distal embolization in PE than with PR, because of the much longer existence of thrombus, 36 which is consistent with the report by Schwartz et al that there was an increase in microvascular occlusion downstream of PE compared with PR. 38 White et al proposed that a residual incidence of MI and stroke was more common and might be attributed to PE. 15 However, Jia et al indicated that PE was related to better myocardial perfusion than PR in STEMI patients.…”
Section: Advance Publication By-j-stagementioning
confidence: 99%
“…15 The platelet fresh component of the thrombus is unstable and prone to embolization into the distal microcirculation, causing MVO and interstitial inflammatory damage. 16 The embolism that occurs several days before the onset of symptoms was recently suggested by In the infarcted wall, MVO could impede coronary blood ejection into the venous circulation and could therefore cancel the benefit conferred in certain cases by coronary collateralization. This increases CWP by means of a large and tall systolic wave that defines the hemodynamic spectrum of MVO.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque erosion contains relatively few macrophages and T cells compared with plaque rupture (Virmani et al, 2000). Thrombotic occlusion is less common with plaque erosion than plaque rupture, whereas microembolization in distal small vessels is more common with plaque erosion than plaque rupture (Schwartz et al, 2009). The proportions of fibrin and platelets differ in coronary thrombi on ruptured and eroded plaques.…”
Section: Pathology Of Atherothrombosismentioning
confidence: 99%
“…Marzilli et al (2000) reported an approximate 80% reduction in coronary blood flow during ischemia in patients with unstable angina. An autopsy study reported that intramyocardial microemboli were frequently present in sudden coronary death patients (Schwartz et al 2009). Distal microvascular embolism and/or vasoconstriction could affect blood flow alteration and thrombus formation and growth at the culprit lesions (Erbel & Heusch, 2000).…”
Section: Altered Blood Flow On Thrombus Growthmentioning
confidence: 99%